2022
DOI: 10.1007/s12528-022-09322-5
|View full text |Cite
|
Sign up to set email alerts
|

Examining key factors of beginner’s continuance intention in blended learning in higher education

Abstract: With the outbreak of the COVID-19 pandemic, blended learning became exceptionally widespread, especially in higher education. As a result, many college students became beginners in this learning method. To identify key factors that impact beginners’ continuance intention in blended learning, this study surveyed 1845 first-year college students at a university in central China in the falls of 2020 and 2021 who used blended learning for the first time. Structural equation modeling was employed to verify a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 41 publications
2
24
0
1
Order By: Relevance
“…Second, more significant improvements in the teacher learning experience can be generated when the design style, tool functions, operation efficiency, and teaching methods of the platforms are optimized. These findings corroborate the previous studies that examined key factors on continuance intention in technology-assisted learning (Yang et al, 2022) and technological barriers to learning outcomes (He and Yang, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Second, more significant improvements in the teacher learning experience can be generated when the design style, tool functions, operation efficiency, and teaching methods of the platforms are optimized. These findings corroborate the previous studies that examined key factors on continuance intention in technology-assisted learning (Yang et al, 2022) and technological barriers to learning outcomes (He and Yang, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The items should be removed if IOC score lower than 0.5 level rating [ 30 ]. At last, 25 items (4 items mearing perceived usefulness [ 12 , 31 , 32 ]; 4 items mearing Satisfaction [ 31 , 33 , 34 ]; 4 items mearing Confirmation [ 35 , 36 ]; 4 items mearing Self-efficacy [ 36 38 ]; 5 items mearing Information Quality [ 31 , 39 , 40 ]; and 4 items mearing Continuance Intention [ 36 , 41 , 42 ] were validated shown as Table 1 . In need of special note that the attention check question (IQ1*) of which meaning was opposite to the IQ1, i.e., “B-learning doesn’t provide me sufficient contents I want” was designed to filter invalid respondents who were randomly choosing the answer without reading contents [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Rahmania et al, (2022) studies students' continuance intention towards e-learning and they investigated all hypotheses of ECM and could establish significant results in case of all except the influence of perceived usefulness on satisfaction. However, Yang et al, (2022) examined the continuance intention of beginners in higher education in blended learning and found significant result for all hypotheses of ECM. Lee (2010) continued with ECM to study continuance intention in e-learning and the findings confirmed the significant influence of satisfaction, perceived usefulness, concentration, subjective norm, attitude, and perceived behavioural control on continuance intention.…”
Section: Expectation Confirmation Modelmentioning
confidence: 99%
“…It states that the confirmation of past expectations will increase the user's perceived usefulness and vice versa. Since the ECM model has been thoroughly covered in the literature (Bhattacherjee, 2001a, b;Bhattacherjee & Premkumar, 2004;Dai et al, 2020;Ouyang et al, 2017;Yang et al, 2022;Rahmania et al, 2022;Suriazdin et al, 2022;Nong et al, 2022;Lee, 2010;Gupta et al, 2020;Malik & Rao, 2019;Jin et al, 2010), the current study just briefly summarises the theory. The conceptual model (Fig.…”
Section: Expectation Confirmation Theory (Ect) and Expectation Confir...mentioning
confidence: 99%